Reinventing Students' Self-esteem in Classrooms: The Need for Humanistic Pedagogy - Bunmi Isaiah Omodan; Nondwe Mtshatsha (STKIP Singkawang, 2022)
Lack of self-esteem among students makes them believe that they are not proficient enough or do not have the needed skills to succeed academically. The perceived lack of self-esteem seems resulting from the observed anti-humanistic teaching and learning system bedevilling all levels of classrooms. Literature confirms that students lack critical thinking skills, relationship skills, and communication skills, which affect their self-esteem. This study is positioned to respond to the issue by presenting humanistic pedagogy as a teaching approach that develops students holistically. It is lensed within the purview of the transformative paradigm since it focuses on how students could be transformed towards gaining the needed self-esteem that will promote their academic, social and societal development. Humanistic Pedagogy theory was presented alongside its principles and assumptions to achieve this. How the assumptions are related to the teaching of humanism and building students' self-esteem was also presented. This study concluded that student-centred classrooms, students' feelings and values, creativity and innovation, and humanising humankind are dimensions of self-esteem development among students. This study recommends that teachers at all levels of education adopt humanistic pedagogical processes in their classrooms.